تحليل المنهج المستقل في تعليم اللغة العربية من المنظور الأوروبي المرجعي المشترك للغات (CEFR) - Sabingatun Dewi Masitoh; Zaenuri, Muhammad; Makruf, Imam; Aji Abdilah, Mokhamad Azis; Albshkar, Hajer Abdallah (UIN ANTASARI, 2024)
This study aims to analyze the independent approach to Arabic language learning in Indonesia using the theoretical perspective of the Common European Framework of Reference for Languages (CEFR). CEFR provides as an international frame of reference language proficiency standards that are regulated on the basis of proficiency levels, ranging from beginner to advanced. This analysis focuses on the alignment between learning outcomes (CP) in the independent curriculum and CEFR standards. This research approach uses a qualitative and descriptive approach, with data collection techniques through documentation and analysis techniques, i.e. content analysis. The results of the study showed that the independent curriculum is consistent with CEFR in the progressive development of receptive and productive language skills. In the A-F phase, there are levels from A1 to B2 when analyzed using the CEFR theorem. This result is expected to be a reference for policymakers in improving curricula to be globally competitive.